Indonesia The Application of Problem Based Learning to the Writing Ability of News Texts of Grade XI Students - Anggia Fenty Nurmaini; Desi Sukenti (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The experimental method was employed in this study to compare the treatment effects between different research groups. Specifically, the research aimed to analyze the application of problem-based learning in enhancing the news text writing abilities of Grade XI students. The study consisted of two action cycles conducted over two sessions. The research participants comprised 29 students in the experimental group and 31 students in the control group, all from Grade XI at SMAN 3 Siak Hulu. Data analysis was conducted using normality tests. The choice of experimental research methodology stemmed from the researchers' intention to administer a specific treatment or intervention to the experimental group. The findings revealed that problem-based learning effectively enhanced news text writing abilities, as evidenced by significant improvements observed in each cycle of the study. During the research phase, the pretest yielded a range of scores, with the highest reaching 79 and the lowest registering at 20. These scores delineated two distinct categories: the lowest and highest values. The lowest score category on the post-test was 65, representing a completion percentage of 43.3%, while the highest score category on the post-test was 95, reflecting a completion percentage of 86.7%. The results underscore the efficacy of problem-based learning in improving students' news text writing abilities, as evidenced by the notable enhancements observed throughout the study. These findings suggest the potential of problem-based learning as an effective instructional approach for cultivating students' writing skills in news text composition.